Primer Design and in Silico PCR for Detection Microsatellite Locus on Cassava (Manihot esculenta) as an Early Study of Genetic Diversity of Gluten Free Food Crops - Ni Putu Senshi Septiasari; Ni Putu Yuni Astriani Dewi (Advances in Tropical Biodiversity and Environmental Sciences, 2024)
Food allergy is a hypersensitive reaction of the body to certain substances that should not be harmful. One of the basic ingredients of foods that are reported to contain allergens is wheat. The type of allergen in wheat is found in gluten, which produces the protein gliadin. The protein gliadin is thought to be the cause of allergic reactions, especially in children and people who have celiac disease. Local food ingredients such as cassava can be used as alternative raw materials for gluten-free food products. The genetic diversity test of cassava is needed to determine the genetic variation of the cassava population and the ability to adapt to natural surroundings. Study of genetic diversity of a plant population can be analyzed by DNA fingerprinting technique using microsatellite molecular markers in the PCR method. Primer selection is a crucial stage because the position of the primer attachment will determine the success of the amplification process. Primer design and in silico PCR assay were carried out as a preliminary study to design the right primer to attach to a specific template. The method used digitally with the help of the NCBI Pick Primer page and FastPCR software for PCR stimulation, knowing the position of the primer attachment, precisely determining the primer and the length of the resulting amplicon. The results obtained in the form of 5 pairs of primer sequences attached to the microsatellite polymorphic locus. The length of the amplicon produced in each primer was 167 bp, 195 bp, 155 bp, 161 bp and 112 bp. The basis of primer selection consists of the length of the primary base, the TM value (melting temperature), the percentage of GC amount and the possibility of the formation of dimers between primers.